Sistem Informasi Pengolahan Data Pasien Rehabilitas Narkoba Menggunakan Metode Web Engineering - Hill Land; Helda Yudiastuti (STMIK Budi Darma, 2023)
The current rapid development of Information Technology is very influential in Processing Rehabilitation Patient Data at BNNP considering that Drug Rehabilitation Patient Data Processing at BNPP still uses the manual method, which is written in a questionnaire. This study aims to create an Information System for Processing Drug Rehabilitation Patient Data at the National Narcotics Agency Website-based South Sumatra Province using the Laravel Framework. This Drug Rehabilitation Patient Data Processing Information System is an internal data processing system such as Doctor's data, Rehabilitation Patient Data, Rehabilitation patient attendance data, Patient Development Data, Counselor Data, doctor data, drug stock and medical record reports of Rehabilitation patients using the Laravel Framework, so that with The existence of this information system will make it easier for admins, counselors and doctors to process rehabilitation and computerized patient data. And the testing method used in this study is a software testing method using black box testing techniques. The results of this study indicate that the information system created is able to work properly and in line with expectations, with a success rate of 95%. This system has a user-friendly interface and makes it easier to process patient data